2021
DOI: 10.1007/s00436-021-07240-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of Acanthamoeba spp. in biofilm communities: a systematic review

Abstract: Acanthamoeba spp. have always caused disease in immunosuppressed patients, but since 1986, they have become a worldwide public health issue by causing infection in healthy contact lens wearers. Amoebae of the Acanthamoeba genus are broadly distributed in nature, living either freely or as parasites, and are frequently associated with biofilms throughout the environment. These biofilms provide the parasite with protection against external aggression, thus favoring its increased pathogeny. This review aims to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 104 publications
1
8
0
Order By: Relevance
“…In our study, from 69 biofilm samples collected from showerheads and kitchen and bathroom sinks, 18 were positive for FLA. Among the positive samples, Acanthamoeba strains were more prevalent than other FLA, which is in accordance with previous studies [16,22,38]. A previous study in Iran reported the presence of FLA in biofilm and dust from hospital wards hosting immunodeficient patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, from 69 biofilm samples collected from showerheads and kitchen and bathroom sinks, 18 were positive for FLA. Among the positive samples, Acanthamoeba strains were more prevalent than other FLA, which is in accordance with previous studies [16,22,38]. A previous study in Iran reported the presence of FLA in biofilm and dust from hospital wards hosting immunodeficient patients.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the Acanthamoeba genus has been found in a wide variety of natural habitats, including biofilms. Previously, the relationship between Acanthamoeba species and biofilms in different places (hospital, aquatic, ophthalmic, and dental environments) revealed that amoebae use biofilms for their survival and the dissemination of pathogens in nature [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that FLAs are able to form biofilm in water supply systems by adhering to each other on a surface (Barbeau & Buhler 2001;Pinto et al 2021). In this regard, dental-unit hydraulic systems contain a high number of long and narrow pipes made of nylon or polyvinyl chloride (Göksay et al 2008).…”
Section: Introductionmentioning
confidence: 99%